PENDIDIKAN BERKESETARAAN GENDER PERSPEKTIF PEMIKIRAN MUHAMMAD ATIYYAH AL-ABRASHI - Syarifah Qamariah (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2017)
This paper examines the gender equality education perspective of Muhammad Attiyah al-Abrashi's thought. Attiyah al-Abrashi is one of the leading figures in education. About twenty of his works speak of education. One interesting study described by 'Attiyah is the issue of liberty and equality education. Gender equality education in the 'Attiyah' perspective is the Islamic recognition of women's right to an unlimited education such as men. This recognition is also supported by historical facts about early educated women. There is freedom for women to learn from basic education to higher education, according to the individual interests of women. Basically the spirit of Islamic education is